Dynamic taping in damage to the long thoracic nerve - proposal proceedings - Filarecka, Agnieszka; Jęchorek, Michał (Journal of Education, Health and Sport, 2020)
Breast cancer is a leading cancer among women, high incidence of cancer is not synonymous with high mortality. Women who undergo radical or partial mastectomy after surgery want to return to full fitness as soon as possible. Movement restrictions associated with the procedure do not have a positive effect on the patients' psyche. One of the complications of surgery in the armpit is long pectoral nerve damage. Impaired mechanics of the shoulder blade affect non-ergonomic movement in the shoulder joint. Using the neurorehabilitation methods, the correct scapula pattern should be restored. Facilitation, i.e. tracking, is also an effective method for peripheral nerve damage. In each of the methods, the movement is supported by a therapist, who can determine the direction of movement through resistance, or support it. The study presents examples of kinesiotaping applications that can be used in therapy at various stages. The method of use depends on the degree of damage to the structure and should be modified for therapy. A review of available literature and own experience were used for the work.